Positive Aspects of Social Networks on The Internet in People's Life - Kurbanov Khurshid (Genius Publishing Group, 2024)
It is no secret that in the information age, modern technologies are increasingly entering our lives. Today, even a kindergarten student is learning to use a mobile phone, its applications and the Internet. It is also true that the number of people who use spiders and spend more time with them increases. Future life is unimaginable without the Internet and the high technologies yet to be discovered. Of course, they have useful properties
Keywords: technologies; information; increasingly; properties